Bohemian Waxwing records, 1982 - Johnson, Tomet al (1982)
Bohemian Waxwing sighting reports contributed by Tom Johnson for January. No year is listed on this handwritten report. Also includes a weather and habitat conditions for June and July 1982. Epson - sheet feed